Pengembangan seni tradisi sebagai penguatan wisata budaya kawasan ekonomi khusus Tanjung Lesung - Yuliawan Kasmahidayat; Rizki Januar Herliawan (Jurnal Abmas, 2023)
This activity is a cross-program collaboration between Dance Education, Music Education, Fine Arts Education, Tourism Education, and Mechanical Engineering at Universitas Pendidikan Indonesia. The form of activity is an assistance program for the development of traditional arts as the flagship of cultural tourism in the Tanjungjaya area. The training model developed in this PKM activity also focuses on material training and HR management. The availability of facilities in this assisted village is sufficient. However, it is not yet supported by the quality of human resources that can utilize and maximize the available facilities and infrastructure. The results obtained from this activity include the development of dance and music as icons of tourist areas, scientific articles, and the presentation of training results in disseminating PKM activity results. The target achievements of this activity also include improving the quality of local human resources to maximize the natural and cultural potential that exists in superior tourism, following the objectives of the tourist village..   Abstrak Kegiatan ini merupakan kolaborasi lintas prodi di Universitas Pendidikan Indonesia antara Prodi Pendidikan Seni Tari, Pendidikan Seni Musik, Pendidikan Seni Rupa, Pendidikan Pariwisata, dan Teknik Mesin. Bentuk kegiatan merupakan pendampingan program pengembangan seni tradisi sebagai unggulan wisata budaya di kawasan Tanjungjaya. Model pelatihan yang dikembangkan dalam kegiatan PKM ini, juga menitikberatkan pada pelatihan materi dan manajemen SDM. Ketersediaan fasilitas di desa binaan ini terbilang cukup, namun belum didukung oleh kualitas sumber daya manusia yang mampu memanfaatkan dan memaksimalkan sarana dan prasarana yang tersedia. Hasil yang diperoleh dari kegiatan ini antara lain bentuk pengembangan seni tari dan musik sebagai icon daerah wisata, artikel ilmiah, serta penyajian hasil pelatihan dalam desiminasi hasil kegiatan PKM. Target capaian dari kegiatan ini di antaranya juga peningkatan kualitas dari SDM setempat, sehingga dapat memaksimalkan potensi alam serta budaya yang ada menjadi wisata unggulan sesuai dengan tujuan desa wisata. Kata Kunci: kawasan ekonomi khusus; KEK; pengembangan seni tradisi; wisata budaya